PENGARUH PERLAKUAN BODY SHAMING TERHADAP KEPERCAYAAN DIRI MAHASISWA BIMBINGAN DAN KONSELING - Siqma Freshtin; Tritjahjo Danny Soesilo; Yustinus Windrawanto (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Along with the development of appearance style and physical character during adolescence, verbal abuse often happen in the form of body shaming. Body shaming are very influential on the self-confidence of adolescents. It’s because in adolescence, self-confidence is very important, especially to build interactions with friends and their environment. Body shaming that a teenager receives will indirectly undermine his self-confidence. This study aims to determine the significance effect of the body shaming treatment towards self-confidence on class of 2020 of Guidance and Counseling students at Satya Wacana Christian University. This type of research is causal comparative. The research sample was taken using a total sampling technique according to the total population of 48 students. The data collection technique uses a questionnaire instrument with 4 alternative answers. The research data were analyzed using a simple linear regression technique using SPSS 23. The results showed that the acquisition of tcount> ttable (-10,220 > 2,013) and a significance value of 0.000 < 0.05. So it can be concluded that in this study there was a negative significant effect of the body shaming treatment towards the self-confidence on class of 2020 Guidance and Counseling students at Satya Wacana Christian University.